Current concepts on microscopic colitis: evidence‐based statements and recommendations of the Spanish Microscopic Colitis Group. Issue 3 (24th November 2015) - Fernández‐Bañares, F.; Casanova, M. J.; Arguedas, Y.; Beltrán, B.; Busquets, D.; Fernández, J. M.; Fernández‐Salazar, L.; García‐Planella, E.; Guagnozzi, D.; Lucendo, A. J.; Manceñido, N.; Marín‐Jiménez, I.; et al.
Summary: Background: Microscopic colitis (MC) is an underdiagnosed inflammatory bowel disease. Aim: To develop an evidence‐based clinical practice guide on MC current concepts. Methods: Literature search was done on the Cochrane Library, EMBASE and MEDLINE electronic databases, which were consulted covering the period up until March 2015. Work groups were selected for each of the reviewed topics, with the purpose of drafting the initial statements and recommendations. They subsequently underwent a voting process based on the Delphi method. Each statement/recommendation was accompanied by the result of the vote the level of evidence, and discussion of the corresponding evidence. The grade of recommendation (GR) using the GRADE approach was established for diagnosis and treatment recommendations. Results: Some key statements and recommendations are: advancing age increases the risk of developing MC, mainly in females. The symptoms of MC and IBS‐D may be similar. If MC is suspected, colonoscopy taking biopsies is mandatory. Treatment with oral budesonide is recommended to induce clinical remission in patients with MC. Oral mesalazine is not recommended in patients with collagenous colitis for the induction of clinical remission. The use of anti‐TNF‐alpha drugs (infliximab, adalimumab) is recommended for the induction of remission in severe cases of MC that fail to respond to corticosteroids or immunomodulators, as an alternative to colectomy. Conclusions: This is the first consensus paper on MC based on GRADE methodology. This initiative may help physicians involved in care of these patients in taking decisions based on evidence.